2010
DOI: 10.1677/joe-10-0064
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor substrate 1 regulates the cellular differentiation and the matrix metallopeptidase expression of preosteoblastic cells

Abstract: Insulin receptor substrate 1 (IRS1) is an essential molecule for the intracellular signaling of IGF1 and insulin, which are potent anabolic regulators of bone metabolism. Osteoblastic IRS1 is essential for maintaining bone turnover; however, the mechanism underlying this regulation remains unclear. To clarify the role of IRS1 in bone metabolism, we employed RNA interference to inhibit IRS1 gene expression and observed the effects of silencing this gene on the proliferation and differentiation of and the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…(39) IRS-1 knockout mice had blunted stimulation of bone turnover after 4 weeks of PTH compared to controls. Knockdown of IRS-1 using RNA interference in cultured osteoblasts leads to impaired collagen-1 synthesis and differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…(39) IRS-1 knockout mice had blunted stimulation of bone turnover after 4 weeks of PTH compared to controls. Knockdown of IRS-1 using RNA interference in cultured osteoblasts leads to impaired collagen-1 synthesis and differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…However, the potential cellular mechanism remains unclear. Several studies have demonstrated that insulin receptor substrates (IRS-1 and IRS-2) that mediate intracellular signaling by insulin and IGF are essential for the RANKL expression in osteoclasts (27)(28)(29). To make clear the potential cellular mechanism of RANKL expression regulated by insulin, future studies can take into account these 2 substrate-mediated signaling pathways activated by insulin in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…MC3T3-E1 cells, a mouse osteoblastic cell line, were kindly provided by Professor Eryuan Liao (19). MC3T3-E1 cells were cultured in α-MEM supplemented with 10% FBS and 1% penicillin-streptomycin in 5% CO 2 at 37˚C.…”
Section: Methodsmentioning
confidence: 99%